Bioactivity of Pseudomonas azotoformans UICC B-91 as an agent with antimicrobial activity, Salmonella typhi and Microsporum canis - Pratiwi, Rina Hidayati; Juliadhi, Reizky (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Infectious diseases caused by bacterial and fungal pathogens remain a major public health concern, particularly in the context of increasing antimicrobial resistance. This study aimed to evaluate the in vitro antimicrobial bioactivity of Pseudomonas azotoformans UICC B-91 extract against Salmonella typhi and Microsporum canis. A quantitative experimental design with a completely randomized design (CRD) was applied using three extract concentrations (30%, 50%, and 100%). Antibacterial activity against S. typhi was assessed using the disc diffusion method, while antifungal activity against M. canis was evaluated using the agar well diffusion method. Inhibition zones were measured and analyzed using SPSS with one-way ANOVA. The results showed that the extract exhibited weak antibacterial activity against S. typhi, with inhibition zones ranging from 1.30 ± 0.28 mm to 2.00 ± 0.71 mm, and statistical significance observed only at the 50% concentration (p = 0.039). In contrast, moderate antifungal activity against M. canis was observed, with a maximum inhibition zone of 6.50 ± 0.71 mm, and ANOVA confirmed a significant effect among treatments (F = 803.936; p = 0.026). These findings indicate that Pseudomonas azotoformans UICC B-91 extract contains bioactive compounds with measurable antimicrobial activity under in vitro conditions, particularly against dermatophyte fungi.